Hydrothermal ore mineralization from the Polish part of the Tatra Mts., Central Western Carpathians - Sitarz, Magdalena; Gołębiowska, Bożena; Nejbert, Krzysztof; Dimitrova, Dimitrina; Milovský, Rastislav (Geology, Geophysics and Environment, 2021)
Several areas with hydrothermal ore mineralization are present in the Polish part of the Western Tatra Mts. Massive and disseminated sulfides, mainly minerals from the tetrahedrite group and chalcopyrite, fill quartz veins accompanied by siderite, dolomite and baryte – many of these were mined between the 16th and 18th century. This paper presents information on the mineralogy of the common sulfides and the preliminary studies of both the isotopic composition of sulfur in tetrahedrite as well as the origin of hydrothermal fluids. The most common primary sulfide minerals in the ores are tetrahedrite-(Zn) and tetrahedrite-(Fe) corresponding to Zn ranges from 1.83 to 5.87 wt.% (0.47–1.44 apfu), and Fe from 1.63 to 5.05 wt.% (0.48–1.52 apfu). The substitution of As for Sb shows maximum As content of 7.25 wt.% (1.588 apfu) which corresponds to the Sb/(Sb+As) = 0.60. Both varieties show substitutions of Bi and Hg, up 0.6 wt.% (0.049 apfu) and 0.96 wt.% (0.081 apfu), respectively, and content of trace elements: Co (max. 976 ppm), Cd (max. 735 ppm), In (max. 14 ppm). Chalcopyrite, pyrite, and galena show compositions close to the ideal formula. Differences in the content of trace elements in the studied tetrahedrite and chalcopyrite were explained by element partitioning between these minerals. The distributions of In, Ga and Sn in the studied minerals indicate that the mineralization was formed at low temperature and pressure. The homogenization temperature of the primary inclusions in quartz in the range of 120–174°C indicate the origin of mineralization in low-temperature stage from low salinity fluids (up to 17.92 wt.% NaCl eq.). Stable δ34S isotopes in minerals of the tetrahedrite group suggest that the igneous fluids might be one of the sources from which ores were crystallized.